Laboratory management for large‐scale population screening for SARS‐CoV‐2. Issue 1 (22nd November 2021) - Duan, Xiuzhi; Lv, Dingfeng; Wang, Lin; Liu, Yanchao; Zhang, Shu; Liu, Weiwei; Xie, Jiamin; Gu, Chunqiang; Li, Xiaosi; Tao, Zhihua; Chen, Xiang; Yao, Qiang
Abstract: Introduction: The aim of this study was to investigate the improvements in laboratory testing procedures and the quality and safety management for large‐scale population screening for severe acute respiratory syndrome coronavirus 2 (SARS‐CoV‐2). Methods: Because of epidemic prevention and control needs in Hebei Province, on January 7, 2021, the Health Commission of Zhejiang Province sent a medical team to Hebei Province, to carry out SARS‐CoV‐2 nucleic acid testing. Screening for the SARS‐CoV‐2 nucleic acid test was performed using reverse‐transcription polymerase chain reaction (RT‐PCR). Practical tests and repeated process optimization were adopted to explore the optimal solution for improving laboratory testing procedures and the quality of and safety management for large‐scale population screening for SARS‐CoV‐2. Results: The Zhejiang medical team completed 250, 000 pooled SARS‐CoV‐2 nucleic acid samples in 24 days in Shijiazhuang, with a peak daily testing capacity of 40, 246 samples testing. There were no false‐negative or false‐positive results, and no laboratory personnel was infected with SARS‐CoV‐2. Significant achievements have been made in SARS‐CoV‐2 prevention and control. Conclusions: This report summarizes the effort of the medical team regarding their management of the quality and safety of laboratory tests and proposes corresponding empirical recommendations to provide a reference for future large‐scale population screening SARS‐CoV‐2. Abstract : The Health Commission of Zhejiang Province of china sent a medical team to Hebei Province, to carry out SARS‐CoV‐2 nucleic acid testing. The Zhejiang medical team completed 250, 000 pooled more than two million peoples' SARS‐CoV‐2 nucleic acid samples in 24 days in Shijiazhuang, with a peak daily testing volume of 40, 246 pooled samples using reverse‐transcription polymerase chain reaction (RT‐PCR). There were no false‐negative or false‐positive results, and no laboratory personnel was infected with SARS‐CoV‐2. Layout recommendations for temporary laboratories for large‐scale nucleic acid screening operation process and experience sharing of each link of nucleic acid detection.